Hatchet - Paulsen, Gary 1939-2021 (Simon & Schuster Books for Young Readers, 2007)
Sequel: The river. -- After a plane crash, thirteen-year-old Brian spends fifty-four days in the Canadian wilderness, learning to survive with only the aid of a hatchet given him by his mother, and learning also to survive his parents' divorce. Includes an introduction and sidebar commentary by the author. -- Newbery Medal Honor Book, 1988.